Repeat pulmonary rehabilitation programs confer similar increases in functional exercise capacity to initial programs - Hill, Kylie; Bansal, V.; Brooks, D.; Goldstein, R. (Lippincott Williams & Wilkins, 2008)
PURPOSE: The benefits of pulmonary rehabilitation (PR) diminish over 12 to 24 months following program completion. In many jurisdictions, patients may be offered a repeat program if they report a decrement in exercise capacity. The aim of this study was to compare measures of functional exercise capacity collected during initial and repeat PR programs. METHODS: A retrospective medical record review was conducted for patients who completed a minimum of 4 consecutive weeks of inpatient PR at our facility in 2001. Measures included the 6-minute walk distance (6MWD) and time to symptom limitation during an endurance walk (EWT) collected prior to and on completion of the initial PR program (year 2001) and, where possible, the first repeat program completed between years 2001 and 2006. RESULTS: Of 76 patients (forced expiratory volume in 1 second = 40 ± 19% predicted; 34 males), 17 repeated PR 25.1 ± 18.4 months after the 2001 program. Change in the 6MWD during the initial program was 37.1 m greater in repeaters than in nonrepeaters (P = .036). In repeaters, the 6MWD measured before commencing the repeat PR program was 45.1 ± 63.7 m lower than the 6MWD measured prior to the initial PR program (P = .013). Improvements in the 6MWD (90.6 ± 70.0 m vs 78.4 ± 83.8 m; P = .43) and the EWT (21 ± 11 minutes vs 21 ± 11 minutes; P = .87) were similar between the initial and repeat programs. CONCLUSION: Similar gains in functional exercise capacity were achieved on completion of initial and repeat PR programs. The large decrement in the 6MWD between PR programs spaced 25 months apart suggests that a shorter time period is needed between programs. © 2008 Lippincott Williams & Wilkins, Inc.